Creating Safe Spaces for Women as an Effort to Prevent Violence Among Junior High School Students - Meilati Suryani; Dedeh Sri Rahayu; Tri Setya Ambarwati (Jurnal Sentra Pengabdian, 2026)
Violence against women remains a global public health and human rights issue that affects women across all age groups, including adolescents. Educational institutions have an important role in creating safe spaces and promoting violence prevention through health education programs. This community service activity aimed to increase junior high school students’ knowledge regarding safe spaces for women and violence prevention through educational interventions. The activity was conducted at one junior high school in Bandung, Indonesia, involving 30 students selected through total sampling. The method used was health education through lectures, discussions, videos, and interactive question-and-answer sessions. Knowledge was measured using pre-test and post-test questionnaires administered before and after the educational session. The results showed that students already had good baseline knowledge before the intervention. However, after the educational activity, there was still an increase in knowledge scores of 0.7%. Students demonstrated better understanding regarding forms of violence, prevention strategies, and the importance of creating safe environments for women and girls. Educational activities in schools can strengthen adolescents’ awareness and attitudes toward violence prevention and support the development of safer school environments. Continuous education programs involving schools, families, and communities are recommended to strengthen sustainable violence prevention efforts among adolescents.